Peningkatan Pendidikan Berbasis Kearifan Lokal Melalui Media Wayang Kulit Sejak Usia Dini - Nur Hasanah, Eli; Hidayatu Munawaroh (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Early childhood education is very fundamental education in providing the basic framework for the formation of subsequent knowledge, attitudes and skills. This research uses a qualitative approach with descriptive research type. This research aims to provide a deep and meaningful learning experience, as well as enrich children's understanding of Indonesia's cultural heritage. Through this approach, it is hoped that a sense of love and pride in local wisdom can grow, foster positive character, and build a solid foundation for children's intellectual and moral development.